Testing NetLogo model code - Steven F. Railsback; Jocelyn Bliven; Volker Grimm; Jacob Kelter (Ecological Modelling, 2026)

Using the ODD protocol and NetLogo to replicate agent-based models - Volker Grimm; Uta Berger; Justin M. Calabrese; Ainara Cortés-Avizanda; Jordi Ferrer; Mathias Franz; Jürgen Groeneveld; Florian Hartig; Oliver Jakoby; Roger Jovani; Stephanie Kramer-Schadt; Tamara Münkemüller; et al. (Ecological Modelling, 2025)

Suboptimal foraging theory: How inaccurate predictions and approximations can make better models of adaptive behavior - Steven F. Railsback (Ecology, 2022)
Optimal foraging theory (OFT) is based on the ecological concept that organisms select behaviors that convey future fitness, and on the mathematical concept of optimization: finding the alternative that provides the best value of a fitness measure. As implemented in, for example, state‐based dynamic modeling, OFT is powerful for one key problem of modern ecology: modeling behavior as a tradeoff among competing fitness elements such as growth, risk avoidance, and reproductive output. However, OFT is not useful for other modern problems such as representing feedbacks within systems of interacting, unique individuals: When we need to model foraging by each of many individuals that interact competitively or synergistically, optimization is impractical or impossible—there are no optimal behaviors. For such problems we can, however, still use the concept of future fitness to model behavior by replacing optimization with less precise (but perhaps more realistic) techniques for ranking alternatives. Instead of simplifying the systems we model until we can find optimal behavior, we can use theory based on inaccurate predictions, coarse approximations, and updating to produce good behavior in more complex and realistic contexts. This so‐called state‐ and prediction‐based theory (SPT) can, for example, produce realistic foraging decisions by each of many unique, interacting individuals when growth rates and predation risks vary over space and time. Because SPT lets us address more natural complexity and more realistic problems, it is more easily tested against more kinds of observation and more useful in management ecology. A simple foraging model illustrates how SPT readily accommodates complexities that make optimization intractable. Other models use SPT to represent contingent decisions (whether to feed or hide, in what patch) that are tradeoffs between growth and predation risk, when both growth and risk vary among hundreds of patches, vary unpredictably over time, depend on characteristics of the individuals, are subject to feedbacks from competition, and change over the daily light cycle. Modern ecology demands theory for tradeoff behaviors in complex contexts that produce feedbacks; when optimization is infeasible, we should not be afraid to use approximate fitness‐seeking methods instead.

Next-Generation Individual-Based Models Integrate Biodiversity and Ecosystems: Yes We Can, and Yes We Must - Volker Grimm; Daniel Ayllón; Steven F. Railsback (Ecosystems, 2017)

Feeding modes in stream salmonid population models: is drift feeding the whole story? - Bret C. Harvey; Steven F. Railsback (Environmental Biology of Fishes, 2014)

Design and Performance of a Channel Reconstruction Project in a Coastal California Gravel-Bed Stream - G. MATHIAS KONDOLF; MATTHEW W. SMELTZER; STEVEN F. RAILSBACK (Environmental Management, 2001)